Karakter Building Upaya Harmonisasi Interaksi Manusia Modern - Otong Surasman (Qiro'ah : Jurnal Pendidikan Agama Islam, 2019)
How important it is to understand and try to get used to practicing positive character in human life, especially humans who live in this modern age. Damage in various fields in Indonesia is the main cause is due to the low character of the community ranging from the upper classes to the lower classes, which is the main cause is due to excessive love for the world and forget the afterlife, so that positive values ​​are currently defeated by negative characters . Therefore, how important it is to re-instill the values ​​of positive character in life, starting from ourselves, our children, immediate family and society in general, in order to re-practice good character in running the wheel of life, so that a full life will be created with fragrance. The realization of a society that is just and prosperous, safe and secure, full of prosperity. Leaders protect the community and the community supports positive government programs. To achieve this goal, then recognize the character of the two main human figures throughout history, namely His Majesty the Prophet Muhammad and the US Ibrahim as the main examples of all time, if you want a better life in the future